Biomedical Engineering: Advances in Micro/Nanoporous Membranes for Biomedical Engineering (Adv. Healthcare Mater. 7/2021). Issue 7 (7th April 2021) - Sun, Meilin; Han, Kai; Hu, Rui; Liu, Dan; Fu, Wenzhu; Liu, Wenming
Abstract : Micro/nanoporous membranes (M/N‐PMs) present quite practical and potential value for extensive biological and medical applications involving separation, patterning, tissue reconstruction, high‐throughput manipulation/analysis, and biosensing. In article number 2001545 by Wenming Liu and co‐workers, the recent advances in fundamentals of micro/nanoporous membranesM/N‐PMs, as well as their applications in biomedical engineering are systematically summarized, providing insights into membrane design, microdevice establishment, and further performance.